Psychomotor availability for school education of 5-6 year old children. - Leschinska K.O (Kharkov National Pedagogical University, 2010)
The relation of physical and mental development of senior preschool children is examined. The received results indicate the necessity of formation management program psychomotor level of availability for schooling with physical education means. The research involved 61 children (33 boys and 28 girls). The school availability by Kern-Irasek test is attained 37,7% of children, 42,6% have a middle school availability and 19,7% are immature. The "Cut the circle" method was performed by 52% of children. The general assessment shows only 48% of children have sufficient availability for school education.